Penerapan Data Mining Algoritma C4.5 Terhadap Prediksi Faktor Menurunnya Hasil Panen Padi - Siahaan, Nove Viktor Boyke; Poningsih, P; Suhendro, Dedi; Hartama, Dedy; Suhada, S (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The aim of the study was to predict the factors causing the decline in rice yields. By knowing the factors of declining rice yields, business owners can further evaluate the causes of declining rice yields and then look for solutions on how to overcome them. The method used in this study is the C4.5 Algorithm, the source of the data used is primary data obtained by direct interviews with rice mill owners and farmers in Siborna Village, Kec. Panei Kab. Simalungun Prov. North Sumatra. The variables used include (1) Pests, (2) Rice Grains, (3) Leaf Color, (4) Planting Month and (5) Planting Method. The results obtained 8 rules for the classification of factors causing the decline in rice yields with 3 increasing decision rules and 5 decreasing decision rules with an accuracy rate of 93.33%. It can be concluded that the predictor of the decline in rice yields is based on the connectedness of the Attributes of Planting Month, Pests, Rice Grains, Leaf Color and Planting Methods.